UK Nutrition Research Partnership 'Hot Topic' workshop report: A 'game changer' for dietary health – addressing the implications of sport sponsorship by food businesses through an innovative interdisciplinary collaboration. Issue 1 (6th December 2021) - Gokani, Nikhil; Garde, Amandine; Philpott, Matthew; Ireland, Robin; Owens, Rebecca; Boyland, Emma
Abstract: Overweight and obesity is a global concern as a significant risk factor for non‐communicable diseases. Increased energy intake due to greater consumption of energy‐dense food or non‐alcoholic beverages high in fat, saturated fat, sugar or salt ('HFSS food') is the main explanation for population weight gain. The principal drivers underlying this consumption are the commercial determinants of health in the food chain, particularly the marketing of HFSS food. In the UK, some rules do regulate certain forms of HFSS food marketing (such as television and online advertising to children) and the government is considering strengthening these. However, although sports sponsorship by 'HFSS food businesses' (defined as a business preparing, cooking, storing, handling, distributing, supplying or selling food and whose products are primarily HFSS) is increasingly recognised as linked to HFSS food consumption, it has received little attention. This is all the more concerning in light of the recent proliferation of 'HFSS food businesses' and HFSS products partnering with sports organisations. Against this background, we hosted a workshop to focus on the relationship between health, nutrition and the sponsorship of sport and related marketing by 'HFSS food businesses' and to consider the implications for obesity prevention strategies in the UK and beyond. This innovative workshop capitalised on, and contributed to, ongoing efforts to conceptually unite existing research by bringing together an interdisciplinary team of experts providing unique and complementary perspectives on how to address sports sponsorship as one of the channels through which 'HFSS food businesses' contribute to poor nutrition and diet‐related diseases. This report summarises the structure, participants and discussions from the workshop; the existing evidence base; and the future research and policy opportunities we plan to pursue.